Cord entanglement in monochorionic monoamniotic twins: a case report - Aggarwal, Preety; Terhase, Nounenuo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Monochorionic monoamniotic twin gestations occur in 1% of all twin pregnancies. They are at increased risk of preterm delivery and acute fetal death. Cord entanglement, malformations, twin to twin transfusion syndrome are responsible for high perinatal mortality and morbidity we report a case of 29 years old primigravida with monoamniotic twins with cord entanglement leading to intrauterine death of both fetuses in MAMC, Agroha.